Pengendalian Konflik Agensi dalam Tahapan Investasi pada Startup dengan Pendanaan Modal Ventura - Mustikoningsih, Ratih; Frensidy, Budi (E-Jurnal Akuntansi; Vol 35 No 2 (2025), 2024)
This research aims to manage agency conflicts such as information asymmetry and moral hazard that occur during the pre-investment to post-investment phases. During the investment process, Venture Capital acts as the principal, while Startups act as the agents. This study employs a qualitative method with a case study approach. The research subjects consist of one (1) Startup in the financial technology (fintech) sector and two (2) Venture Capital firms, one owned by a State-Owned Enterprise (SOE) and the other privately owned. The findings indicate that managing agency conflicts between Venture Capital and Startups requires comprehensive pre-investment assessments, including initial selection that covers financial and non-financial aspects, as well as contractual agreements involving a due diligence process. Meanwhile, post-investment management is carried out through performance monitoring, staged funding, and forming a Venture Capital Syndicate. Keywords: Agency Conflict; Moral Hazard; Information Asymmetry; Venture Capital; Startup.